The Potential of the Land Value Capture Scheme in the Perspective of Disaster Risk Funding - Handayani, Alfita Puspa; Hanif, Alifah; Meilano, Irwan (TDMRC, Universitas Syiah Kuala, 2023)
Disaster risk refers to the possibility of a loss of life, assets, health, and livelihoods to the community in the future, so it must be reduced, one of which is by implementing disaster risk management. The disaster risk management financing scheme is crucial considering the number of funds needed. This research serves as an initial exploration into alternative funding options by investigating the potential benefits of implementing the Land Value Capture (LVC) scheme. The driving question of this study focuses on the advantages of employing the land value capture concept for disaster risk funding. To address this question, a descriptive qualitative research methodology is employed, encompassing an analysis of LVC in general, a funding analysis for disaster risk management, and the implementation of LVC for disaster risk reduction specifically in Indonesia. The findings of this study reveal that the Land Value Capture (LVC) scheme can serve as an additional strategy for funding disaster risk management in Indonesia. Through the proposed framework, the integration of LVC with disaster risk financing and insurance is facilitated.